Noite Lilás (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Noite Lilás is a cabaret performance born from the interdisciplinarity between the fields of theater, music and visual arts. From the formation of a tableau vivant of the painting Metropolis, by Otto Dix, the singer-actresses and musicians assume figures based on the universe of the grotesque to sing and narrate the different cabaret scenes. This was an experience carried out based on the subjects of Voice IV (DAC), Pictorial Interlocutions (DAV) and Theatrical Interpretation IV (DAC), which took place throughout the year 2022.
Keywords: theatrical production; performance; Cabaret; grotesque